(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This article explores the methodological foundations for developing a bilingual communicative environment in primary education through the lens of Waldorf pedagogy. The aim is to identify how the Waldorf educational framework- rooted in the holistic development of the child- can support the natural acquisition of a second language in early school years. Through theoretical analysis, case study observations, and review of empirical research, this study demonstrates that imitation-based learning, storytelling, rhythmic speech, and integration of artistic activities foster a rich bilingual environment. The results suggest that Waldorf principles align well with communicative language teaching (CLT), offering alternative, and emotionally engaging ways to support multilingual development in children.